Mapping the manuals of madness: Comparing the ICD‐10 and DSM‐IV‐TR using a network approach - Tio, Pia (Int J Methods Psychiatr Res, 2016)
The International Classification of Diseases and Related Health Problems (ICD) and the Diagnostic and Statistical Manual of Mental Disorders (DSM) represent dominant approaches to diagnosis of mental disorders. However, it is unclear how these alternative systems relate to each other when taking into account the symptoms that make up the disorders. This study uses a network approach to investigate the overlap in structure between diagnostic networks pertaining to ICD‐10 and DSM‐IV‐TR. Networks are constructed by representing individual symptoms as nodes, and connecting nodes whenever the corresponding symptoms feature as diagnostic criteria for the same mental disorder. Results indicate that, relative to the DSM‐IV‐TR network, the ICD‐10 network contains (a) more nodes, (b) lower level of clustering, and (c) a higher level of connectivity. Both networks show features of a small world, and have similar (of “the same”) high centrality nodes. Comparison to empirical data indicates that the DSM‐IV‐TR network structure follows comorbidity rates more closely than the ICD‐10 network structure. We conclude that, despite their apparent likeness, ICD‐10 and DSM‐IV‐TR harbour important structural differences, and that both may be improved by matching diagnostic categories more closely to empirically determined network structures. Copyright © 2016 John Wiley & Sons, Ltd.